IMPLEMENTASI METODOLOGI PENDIDIKAN DALAM AL-QURAN DAN HADIS - Nasir, M.; Muharir; Subhi, Muhibbul (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2024)
This research aims to explain the Implementation of Educational Methodology in the Qur'an and Hadith. The type of research used in this study is a literature study using a descriptive analysis approach method. This research is carried out by collecting various kinds of information and studying literature related to the methodology of education in Islam contained in the Qur'an and Hadith. The results of this study show that the Qur'an and Hadith have a significant role, especially in the perfect application of Islamic education to students. It can help students better understand Islamic religious teachings and how to practice them in daily life, and it can help increase students' interest and motivation in learning. Educational methodologies in the Qur'an and Hadith are also important for educators and students to understand the basic principles of Islamic education based on the Qur'an and Hadith, develop communication skills, speaking ethics, commendable morals and understand students' physical and spiritual needs.